Electron beam irradiation preserves organic acids in Agaricus bisporus Portobello - Cardoso, Rossana V.C. (2018)
The analysis of organic acids hás become increasingly important due to the role of these compounds in the physiological activity of plants and mushrooms, exerting a determinant activity in maintaining their quality and organoleptic characteristics. Furthermore, organic acids profile hás been continuously used as a quality control indicator [l], The short shelflife ofmushrooms is a barrier to their distribution and, therefore, there hás been extensive research to find technologies that ensure the preservation of mushrooms, maintaining their organoleptic properties. Irradiation is an alternative that hás already been successfully applied in various food products [2]. In the present study, the efFects of electron beam irradiation and storage period (0, 4 and 8 days) over the organic acids profile ofthe widely cultivated mushroom Agaricus bisporus Portobello, were evaluated. The irradiation was performed with a 10 MeV energy irradiator at the doses of l, 2 and 5 kGy and organic acids were determined using ultrafast liquid chromatograph (UFLC) coupled to photodiode array detector (PDA) and 215 nm as preferred wavelengths, using a Shimadzu 20A series UFLC (Shimadzu Cooperation). In general, irradiated samples conducted to higher concentrations of ali the quantified organic acids (oxalic, quinic and malic acids), particularly when using 2 and 5 kGy doses (ranging between 0.6 - 1.8 g/lOOg and 0.6 - 1.9 g/lOOg respectively). Overall, irradiation might be an alternative process to extend the shelf-life of mushrooms, while preserving the composition in organic acids.